Hydrodynamic and experimental characterization of pumps as turbines - Daniel Felipe Tobón-Espinosa; David Alejandro Mejía-Ocampo; Ricardo Moreno-Sánchez; Francisco Javier Botero-Herrera (Dyna, 2023)
To estimate the performance, efficacy, modes of operation, hydrodynamic instabilities, and methodologies for harnessing energy from the pump as turbine (PAT), it is necessary to characterize these hydraulic turbomachines in all their modes of operation using an experimental test rig that simulates actual operating conditions. In this process, the characteristic curve of four quadrants of a turbomachine is constructed, especially its five modes: pump mode, brake pump mode, turbine mode, brake turbine mode, and reverse pump mode. In addition, with dynamic sensors installed in the pump volute, it is possible to know the hydrodynamic phenomena within PAT, finding its average behavior and frequency response, which is a tool for diagnosing the machine’s condition.